Diagnóstico serológico de Fasciola hepatica en ovinos de Boavita (Colombia) - Bulla-Castañeda, Diana-María; Ortiz-Pineda, Melissa-Camila; Cruz-Estupiñan, Sharon-Elizabeth; Lopez-Buitrago, Henrry-Alexander; Lancheros-Buitrago, Deisy-Johana; Giraldo-Forero, Julio-Cesar; Garcia-Corredor, Diego-Jose; Pulido-Medellin, Martin-Orlando (Revista Científica, 2023)
Fasciolosis is a worldwide disease caused by the trematode Fasciola hepatica, which affects cattle, sheep, goats, and sometimes humans, causing significant economic and production losses. The objective of this study was to determine the seroprevalence of F. hepatica in sheep from Boavita, Boyacá, Colombia. An observational, descriptive cross-sectional study was carried out with simple random sampling, where the sample size was 297 sheep. The sera were processed with the commercial ELISA BIO K 211-Monoscreen AbELISA F. hepatica kit, following the manufacturer's instructions. The analysis of the results was carried out with the statistical program Epi Info®. A general seroprevalence of 67.34% was determined, where males, sheep older than 3 years, and Creole sheep presented the highest seroprevalence, with 77.78, 83.33, and 64.79%, respectively. A significant statistical association was established between seropositivity to F. hepatica and sheep aged 1 to 3 and individuals older than 3 years. This age group was established as a risk factor for the manifestation of fasciolosis, whereas sheep between 1 to 3 years old were considered as a protective factor. Management variables such as extensive and stake grazing also showed statistical significance, the latter being a protective factor for parasitosis. Our findings show the spread of F. hepatica infections in sheep and confirm the importance of serological methods for the diagnosis of the disease.